CYP3A5 genotype and its impact on vincristine pharmacokinetics and development of neuropathy in Kenyan children with cancer - Skiles, Jodi L.; Chiang, ChienWei; Li, Claire H.; Martin, Steve; Smith, Ellen L.; Olbara, Gilbert; Jones, David R.; Vik, Terry A.; Mostert, Saskia; Abbink, Floor; Kaspers, Gertjan J.; Li, Lang; et al. (Pediatric blood & cancer, 2018)
Background Vincristine (VCR) is a critical part of treatment in pediatric malignancies and is associated with dose‐dependent peripheral neuropathy (vincristine‐induced peripheral neuropathy [VIPN]). Our previous findings show VCR metabolism is regulated by the CYP3A5 gene. Individuals who are low CYP3A5 expressers metabolize VCR slower and experience more severe VIPN as compared to high expressers. Preliminary observations suggest that Caucasians experience more severe VIPN as compared to nonCaucasians. Procedure Kenyan children with cancer who were undergoing treatment including VCR were recruited for a prospective cohort study. Patients received IV VCR 2 mg/m2/dose with a maximum dose of 2.5 mg as part of standard treatment protocols. VCR pharmacokinetics (PK) sampling was collected via dried blood spot cards and genotyping was conducted for common functional variants in CYP3A5, multi‐drug resistance 1 (MDR1), and microtubule‐associated protein tau (MAPT). VIPN was assessed using five neuropathy tools. Results The majority of subjects (91%) were CYP3A5 high‐expresser genotype. CYP3A5 low‐expresser genotype subjects had a significantly higher dose and body surface area normalized area under the curve than CYP3A5 high‐expresser genotype subjects (0.28 ± 0.15 hr·m2/l vs. 0.15 ± 0.011 hr·m2/l, P = 0.027). Regardless of which assessment tool was utilized, minimal neuropathy was detected in this cohort. There was no difference in the presence or severity of neuropathy assessed between CYP3A5 high‐ and low‐expresser genotype groups. Conclusion Genetic factors are associated with VCR PK. Due to the minimal neuropathy observed in this cohort, there was no demonstrable association between genetic factors or VCR PK with development of VIPN. Further studies are needed to determine the role of genetic factors in optimizing dosing of VCR for maximal benefit.